The effect of social settings and olfactory environments on spontaneous movement synchrony - M. R. Coeugnet; Y. N. Delevoye-Turrell; W. Tschacher; J. Coutinho (Scientific Reports)
Abstract Interpersonal synchrony refers to the temporal coordination between two individuals, signaling the coupling of their behaviors. Optimal movement synchrony in dyads is linked to more affiliative behavior, cooperation, and trust. However, there is limited research on how the sensory environment impacts interpersonal synchrony. One significant environmental factor influencing human behavior and social interactions is ambient odors. This study aimed to examine the effect of ambient odor on interpersonal synchrony, particularly in-phase movement synchrony. Motion energy analysis and windowed cross-correlations were used to measure synchrony levels between participants during video-recorded interactions. Twenty-five same-sex friend dyads performed three interaction tasks designed to create fun, cooperative, or competitive atmospheres. These tasks were conducted with a pleasant, stimulating peppermint odor or in a control condition without odor. Consistent with previous studies, higher synchrony levels were observed in fun atmospheres compared to competitive and cooperative ones. No significant effects of odor stimulation were found. Overall, the results confirm that social context significantly influences movement synchrony and affiliation, while ambient odor might not affect interpersonal synchrony, at least when the odor is irrelevant to the task.